Curricular renewals in health sciences programs and its impact on professors' teaching practices. - Lesmes JD (Revista Ciencias de la Salud)
The article is an advance of a research project entitled 'Transformations in professors' teaching practices in a curriculum renewal process', which is based on a conceptual framework that arises from the analysis of four main elements to address the issue: The first one refers to the concept of 'curriculum', which involves different aspects of the actors that take part in education. The second main element has to do with curriculum renewal in Health Sciences Programs, so it helps to clarify and determinate how the academic community understands renewal, in terms of characteristics, purposes and effects. The third element, 'curriculum renewals in Health Sciences Programs and teaching practices', allows the analysis of the information in order to determine the enabling factors to appropriate or non-appropriate principles of curriculum renewal, reflected in professor's teaching practices. And in the fourth main element, conceptualizations in relation to learning and teaching practices are explored to identify how teachers interpret and lead their educational act. Finally, a discussion is proposed, regarding the answering of the following questions: how do processes of curriculum renewal in Health Sciences professional formation programs impact the teaching practices of professors? And, what factors make possible the appropriation of the principles of curriculum renewal in professors' teaching practices in Health Sciences professional formation programs?